2019
DOI: 10.1515/geo-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Potential influence of meteorological variables on forest fire risk in Serbia during the period 2000-2017

Abstract: To examine potential relationships between meteorological variables and forest fires in Serbia, daily temperature, precipitation, relative humidity and wind speed data for 15 meteorological stations across Serbia were used to construct fire indices. The daily values of the Ångström and Nesterov indices were calculated for the period 2000-2017. A high number of forest fires occurred in 2007 and 2012 in Serbia, during a period of extremely high air temperatures in 2007, followed by the longest heat wave and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…Our FWI values were similar to those of other Chinese provinces where the FWI values were linked to fire (Lynham and Stocks 1989;Tian et al 2011Tian et al , 2014Yang and Di 2011). More studies had found a strong relationship between FWI and wildfire occurrence in other regions, like the Mediterranean, south-east and Central Europe (Good et al 2008;Dimitrakopoulos et al 2011;De Jong et al 2016;Bedia et al 2018;Lahaye et al 2018;Fernandes 2019), Russia (Tosic et al 2019), Australia (Dowdy et al 2010), and on the global scale (Field et al 2015). Our results showed that the FWI value in the interval from October 21 to 28 exceeded 13.95 and approached 20.67, which corresponds to more than 30 and 170 ha of burnt forest, respectively, according to Xanthopoulos et al (2014) scale.…”
Section: Validity Of the Fwi System For Fire Risk Management In Typical Temperate Forests In Chinasupporting
confidence: 86%
“…Our FWI values were similar to those of other Chinese provinces where the FWI values were linked to fire (Lynham and Stocks 1989;Tian et al 2011Tian et al , 2014Yang and Di 2011). More studies had found a strong relationship between FWI and wildfire occurrence in other regions, like the Mediterranean, south-east and Central Europe (Good et al 2008;Dimitrakopoulos et al 2011;De Jong et al 2016;Bedia et al 2018;Lahaye et al 2018;Fernandes 2019), Russia (Tosic et al 2019), Australia (Dowdy et al 2010), and on the global scale (Field et al 2015). Our results showed that the FWI value in the interval from October 21 to 28 exceeded 13.95 and approached 20.67, which corresponds to more than 30 and 170 ha of burnt forest, respectively, according to Xanthopoulos et al (2014) scale.…”
Section: Validity Of the Fwi System For Fire Risk Management In Typical Temperate Forests In Chinasupporting
confidence: 86%
“…Both indices are simple fire danger indicator, but they can be very successful. Studies [10,12] showed that the relationship between forest fires and fire indices existed in different regions of Serbia. In order to improve the wildfire risk assessment, the Angstrom index was modified, and a significant correlation with the forest fires is found in southern Serbia [25].…”
Section: Correlation With Forest Firesmentioning
confidence: 99%
“…The risk of forest fires caused by the drought is the greatest in August and July in Serbia [11]. To examine potential relationships between meteorological variables and forest fires in Serbia, daily temperature, precipitation, relative humidity, and wind speed data for fifteen meteorological stations across Serbia are used [12]. They found that using relative humidity or precipitation as a predictor only generates a satisfactory model for forecasting of number of forest fires (NFF).…”
Section: Introductionmentioning
confidence: 99%
“…When studying forest fires, two aspects arise: what data to use and in what territorial boundaries to analyze this data. In general, forest fires are investigated using statistical, satellite and meteorological data [1][2][3][4][5]. Statistics can be: official data of public bodies (ministries and departments); press releases and industry magazines.…”
Section: Introductionmentioning
confidence: 99%
“…all examined potential links between meteorological variables and forest fires in Serbia. For this purpose, data on daily temperature, precipitation, relative humidity and wind speed were used from 15 weather stations across of Serbia [5].…”
Section: Introductionmentioning
confidence: 99%